Sources of polychlorinated biphenyls (PCBs) and dichlorodiphenyltrichloroethanes (DDTs) found in surface sediment from coastal areas of Beibu Gulf: A reflection on shipping activities and coastal industries - Lao, Qibin; Liu, Guoqiang; Zhou, Xin; Chen, Fajin; Zhang, Shuwen (Marine pollution bulletin, 2021)
The presence of polychlorinated biphenyls (PCBs) and dichlorodiphenyltrichloroethanes (DDTs) was determined in the sediments of Beibu Gulf, a newly developing industry and port in South China, to evaluate whether the rapid development of coastal cities has accelerated the organic pollution in the region. The levels of PCBs and DDTs ranged from 1.17 to 8.00 ng g−1 and ND (not detected) to 3.82 ng g−1, respectively. The levels were higher in the east of Beibu Gulf than in the west, which influenced by the industrialisation and urbanisation in the east. Additionally, penta-PCBs were the dominant PCB congeners, which are related to shipping activities, and DDTs may have originated from the historical use of technical DDT. The levels of pp′-DDD and PCBs did not have the potential to cause ecological risks in Beibu Gulf; however, residues of DDTs were at relatively higher ecotoxicological levels, thereby having the potential to cause adverse biological effects. •PCBs and DDTs were ubiquitous in the sediments of Beibu Gulf, South China.•High levels of PCBs and DDTs were observed in the east of Beibu Gulf.•36% of PCB congeners were sourced from shipping activities.•DDTs would have the potential to cause adverse biological effects.